1.7 µm tunable picosecond-pulsed fiber light source based on nonlinear effect combination using a cascaded intensity modulator. (3rd July 2018) - Zhang, Peng; Wu, Di; Li, Xiaoyan; He, Zhenxing; Zhang, Xinmeng; Chen, Junda; Han, Kexuan; Wang, Tianshu; Zhang, Lizhong; Tong, Shoufeng; Jiang, Huilin
Abstract: A tunable, picosecond-pulse fiber light source based on nonlinear effect combination around 1.7 µ m is proposed and experimentally demonstrated. In our scheme, a continuous wave laser and a cascaded intensity modulator are employed as a pump source in order to generate pulse trains with switched repetition and pulse duration. The configuration includes a 1 km long high nonlinear fiber used as the gain medium. A picosecond-pulsed supercontinuum can be obtained by pumping the amplified pulse train; it is then modified by wavelength division multiplexing. Additionally, a tunable filter can be employed for filtering out the tunable picosecond-pulsed fiber light source near 1.7 µ m. As a result, this light source generates a 200 MHz pulse train with wavelength tuning from 1660.1 nm to 1703.7 nm, and the pulse duration of the source is estimated as 151 ps. The repetition can be switched in a range (100 MHz–200 MHz). The tunable repetition range could be limited by low contract of intensity modulators, characteristics of delay and an erbium-doped fiber amplifier.